KINERJA GURU SEKOLAH DASAR NEGERI SOULUWE KECAMATAN DOLO KABUPATEN SIGI - Katip, Selfian (Katalogis, 2018)
The aims of this study was to determine the teacher performance in Soulowe ElementarySchool of Dolo Sub-district, Sigi. The main theory used in this research is the theory advanced by Mathis and Jackson that there are three main factors that affect how individuals are there to work and to support performance, that is the individual's ability to do the job, level of effort devoted, and support organizations. The research location is an Soluwe Elementary School of DoloSub-district,Sigi. Informant as much as 5 people were selected purposively. The data collection was done by interviewing, observation, and documentation. Analysis using Interactive model of Miles and Huberman. The research concludes that the performance of teachers at SDN Souluwe in improving the quality of education is still not good. The results of this study revealed that teacher performance is not good, is closely related to the ability of teachers are still not good in performing their duties which is in the process of learning in schools, the level of effort that is not maximal poured out by teachers in order to improve the quality of education and is still a lack of internal support in the process SDN Souluwe learning.